Causal structure and the geodesics in the hairy extension of the Bertotti-Robinson spacetime - Memari, Vahideh; Mazharimousavi, S. Habib (Iop Publishing Ltd, 2023)
A hairy extension of the Bertotti-Robinson regular spacetime has been recently introduced in the context of the Einstein-Maxwell-Scaler theory that surprisingly is a singular black hole formed in the S (3) background spatial topology [CQG39(2022)167001]. In this research, we first clarify the topology of the spacetime based on the coordinate transformations as well as the energy-momentum configuration and the causal structure of the black hole. Furthermore, we investigate the geodesics of the null and timelike particles in this spacetime. It is shown that in the radial motion on the equatorial plane, while photons may collapse to the singularity or escape to the edge of the Universe, a massive particle always collapses to the singularity. The general geodesics of null and massive particles reveal that all particles except the outgoing light ray, eventually fall into the black hole.
Keywords: geodesics; bertotti-robinson; closed black hole; causal structure